From Reviews To Revenue: The Role of Product Quality, Online Customer Review and Brand Image in Samsung's Shopee Application Sales - Kuswibowo, Christian; Santoso, Agus; Saberan, Fauzi; Raharjo, Tri (School of Business, IPB University (SB-IPB), 2025)
Background: The growth of e-commerce had transformed consumer purchasing behavior, particularly in online marketplaces like Shopee. Samsung, a leading smartphone brand, relied on product quality and online customer reviews to influence consumer decisions. This study examined how these factors shaped purchasing decisions, with brand image serving as a mediating variable in this relationship.Purpose: This study explores how product quality and online customer reviews affect purchasing decisions, considering brand image as a mediating factor.Design/methodology/approach: A quantitative research approach was employed utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze the relationships between the studied variables. Data were gathered from 160 Shopee users through structured questionnaires, analyzing the relationships between product quality, online customer reviews, brand image, and purchasing decisions using convenience sampling.Finding/Result: Findings show that product quality and brand image strongly influenced purchase intent, while online reviews affected brand image but not purchasing decisions, underscoring the key role of brand perception in e-commerce.Conclusion: This study confirmed that product quality and brand image were key determinants of purchasing behavior, emphasizing the importance of brand perception in online consumer decision-making.Originality/value (State of the art): This study enriches the existing digital marketing literature by exploring the integrated impact of product quality and online customer reviews on consumer purchase decisions, with brand image serving as an intermediary factor. The findings provide valuable insights for e-commerce businesses, enabling them to refine branding strategies, strengthen consumer trust, and enhance overall online sales performance. Keywords: product quality, online customer reviews, brand image, purchasing decisions, consumer behavior